International Fuel Tax Assessment : An Application to Chile - Parry, Ian (IMF Working Papers; Working Paper ;, 2011)
Gasoline and diesel fuel are heavily taxed in many developed and some emerging and developing countries. Outside of the United States and Europe, however, there has been little attempt to quantify the external costs of vehicle use, so policymakers lack guidance on whether prevailing tax rates are economically efficient. This paper develops a general approach for estimating motor vehicle externalities, and hence corrective taxes on gasoline and diesel, based on pooling local data with extrapolations from U.S.evidence. The analysis is illustrated for the case of Chile, though it could be applied to other countries.